Kritik atas Kritik Kamaruddin Amin terhadap Riwayat Mudallisin dalam Sahih al-Bukhari dan Sahih Muslim - Syukrillah, M. (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2017)
This research is prompted by the thought of Kamaruddin Amin, who challenges the concept of Ulum al-Hadith regarding the transmission of mudallisin in Sahih al-Bukhari and Sahih Muslim. The article finds that: first, there have been inconsistencies and gaps between the theory and practice in the concept of tadlis; second, there are negative implications of application of tadlis according to Ulum al-Hadith against the transmission of mudallisin; third, Sighat al-Tahammul wa al-Ada' has no significance either in the study of Hadith authentication in general or in the context of tadlis in particular; fourth, Nasr al-Din al-Albani's method of determining the authenticity of mudallas Hadith has a weakness and negative implications upon mudallas Hadiths in general; fifth, the application of mudallas Hadith criticism according to the traditional method using al-jarh muqaddam 'ala al-ta'dil idha kana mufassaran when the controversy occurs in the assessment of the predicate of a Hadith; and sixth, orientalist alis method of giving the calendar to the Hadith can be used as an alternative way to overcome the weaknesses of the method of classical Hadith science.